The EPA between the UE and África. The introduction of reciprocity and the case of Ghana - Valera Fernández, Eva (Papeles de Europa, 2012)
Under the Cotonou Agreement, the European Union (EU) is negotiating the Economic Partnership Agreements (EPA) with the different regions of the countries African, Caribbean and Pacific (ACP) where trade reciprocity is introduced. Taking the case of the provisional EPA that is meant to be signed between the EU and Ghana, this paper describes and analyzes the characteristics of the Agreement and its consequences for the African country. It also criticizes the premature introduction of the reciprocity in the trade between both regions.